Relationship of Social and Behavioral Characteristics to Suicidality in Community Adolescents With Self-Harm: Considering Contagion and Connection on Social Media - Seong, Eunice; Noh, Gahye; Lee, Kyung Hwa; Lee, Jong-Sun; Kim, Sojung; Seo, Dong Gi; Yoo, Jae Hyun; Hwang, Hyunchan; Choi, Chi-Hyun; Han, Doug Hyun; Hong, Soon-Beom; Kim, Jae-Won (Frontiers in Psychology, 2021)
A close link has been established between self-harm and suicide risk in adolescents, and increasing attention is given to social media as possibly involved in this relationship. It is important to identify indicators of suicidality (i.e., suicide ideation or attempt) including aspects related to contagion on social media (e.g., exposure to self-harm posts), and explore how social media can intervene in the relationship between social circumstances and suicidality in young adolescents with self-harm. This study explored characteristics of Korean adolescents with a recent history of self-harm and identified how behavioral and social features explain lifetime suicidality with emphasis on the impact of social media. Data came from a nationwide online survey among sixth- to ninth-graders with self-harm during the past 12 months (n=906). We used χ2 tests of independence to explore potential concomitants of lifetime suicidality and employed a multivariate logistic regression model to examine the relationship between the explanatory variables and suicidality. Sensitivity analyses were performed with lifetime suicide attempt in place of lifetime suicidality. Having endorsed moderate/severe forms and multiple forms of self-harm (OR 5.36, p<.001; OR 3.13, p<.001), having engaged in self-harm for two years or more (OR 2.42, p=.001), having friends who self-harm (OR 1.92, p=.013), and having been bullied at school were associated with an increased odds of lifetime suicidality (OR 2.08, p=.004). Notably, having posted content about one’s self-harm on social media during the past 12 months was associated with an increased odds of lifetime suicidality (OR 3.15, p<.001), whereas having seen related content in the same period was not. Sensitivity analyses yielded similar results with lifetime suicide attempt, supporting our findings from the logistic regression. The current study suggests that self-harm may be prevalent from early adolescence in Korea with assortative gathering. The relationship of vulnerable adolescents’ social circumstances (e.g., peer relationship) to suicide risk may be compounded by the role of social media. As the impact of social media may be connected to both risk (i.e., contagion) and benefit (i.e., connection and support), pre-existing vulnerabilities alongside SH and what online communication centers on should be a focus of clinical attention.